192 Primary care streaming in emergency departments- contexts and mechanisms associated with perceived effectiveness outcomes: a realist evaluation. Issue 12 (23rd November 2020) - Edwards, Michelle; Edwards, Michelle; Cooper, Alison; Davies, Freya; Stevens, Andrew Carson; Hughes, Thomas; Anderson, Pippa; Edwards, Adrian
Abstract : Aims/Objectives/Background: Recent policy has encouraged emergency departments (EDs) to deploy nurses to stream patients from the ED front door to GPs working in a separate GP service operating within or alongside an ED. We aim to describe mechanisms relating to effectiveness of streaming in different primary care service models identified in emergency departments. We explored whether patients were appropriately streamed to emergency care, primary care, other hospital services or community primary care services; patient flow (including effects on waiting times and length of stay in the emergency department); and safe streaming outcomes. We sought suggestions for quality improvements relating to streaming Methods/Design: A realist evaluation methodology was used to explore perceived streaming effectiveness. We visited 13 emergency departments (purposively selected across England & Wales; 8 streamed primary care patients to a primary care clinician) and carried out observations of triage/streaming and patient flow and interviews with key members of staff (consultants, GPs, nurses).Field notes from observations and audio-recorded interviews were transcribed verbatim and were analysed by creating context, mechanism and outcome configurations to refine and develop theories relating to streaming effectiveness. Results/Conclusions: We identified five contexts (nurses' knowledge and experience, streaming guidance, teamwork and communication, operational management and strategic management) that facilitated mechanisms that influenced the effectiveness of streaming (streaming to an appropriate service, patient flow, delivering safe care). We integrated a middle range psychological theory with our findings to recommend a focus for training nurses in streaming and service improvements. We recommend a collaborative approach to service development, guidance and training (including input from emergency department clinicians, primary care clinicians) and a range of training strategies that are suitable for less experienced junior nurses and more experienced senior nurses and nurse practitioners.